Graphic displays: the effects of orientation on the tangible perception of histograms and pie charts - Painter, J; Pring, L (International journal of rehabilitation research, 2000)
Two studies designed to investigate the ability of blind subjects to interpret tangible graphic displays of data at varying degrees of orientation are reported. In the first experiment visually handicapped children were required to interpret histograms and pie charts presented at two different orientations. Horizontally oriented histograms were found to have a significant advantage over vertically oriented histograms, but there was no effect of orientation on pie charts. In the second study horizontally and vertically oriented histograms were again compared using a subject sample comprised only of congenitally or very early blind children. The results confirmed the superiority of horizontally presented histograms over the more common vertical display.